A Legal Analysis of the Constitutional Disputes Between the Iraqi Government and the Kurdistan Region (2005- 2013) - Nigar Dler Ahmad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research paper will make a comprehensive legal analysis of the constitutional disputes between the Iraqi Federal and Kurdistan Regional Government in a way that authorities are divided between the Iraqi Federal Government and the Kurdistan Regional Government, Powers Exclusively Given to the Federal Government, Powers Shared Between the Iraqi Federal and the Kurdistan Regional Government and Powers that are Neither Given Exclusively nor Shared. This paper also discusses those conflicts that arise about the distribution of powers in the Iraqi constitution between the Iraqi Federal Government and Kurdistan Regional Government. Constitutional problems include oil and gas disagreements, disputed territorial areas between Iraq and the Kurdistan Region, article 140 in Iraqi constitution, and other issues including budget.